Students as partners: the development of an extensive reading program at the Ningbo Campus of the University of Nottingham - Sturman, Peter; Zheng, Yangyang; Peng, Lexiao; Lamb, Doran (Journal of Educational Innovation, Partnership and Change, 2018)
"Changing Reading Circles brought more than we expected: we also changed ourselves". A reading interest group at the University of Nottingham Ningbo China was changed to an employability award by a team of five students and two staff partners by the use of a Students as Change Agents student/staff partnership project. Responsibility and authority was devolved to students and the final product has resulted in more engagement in, and enthusiasm for, extensive reading. It also gave the student partners greater levels of self-belief, autonomy and understanding of their potential within an academic community.